Polish-German bilingualism at school. A Polish perspective - Pulaczewska, Hanna (Linguistik Online, 2014)
This article presents the institutional frames for the acquisition of Polish literacy skills in Germany and the maintenance of Polish-German bilingualism after the repatriation of bilingual children to Poland. These processes are examined in the context of recent developments in the European domestic job market. While the European Union has placed proficiency in several languages among its educational objectives, and foreign languages have been made obligatory school subjects in all member countries, the potential advantages of internal European migrations for producing high-proficiency bilinguals are being ignored. Bilingualism resulting from migration and biculturalism enjoys little social prestige in the host countries. In Germany, there is significant regional variation in how school authorities react to challenges posed by the presence of minority languages. In many cases, the linguistic potential of many second-generation migrants and re-emigrants gets largely wasted because of lacking interest and incentives from German and Polish institutions alike.